Advertisement Remove all ads

Using properties of determinants, prove that |((x+y)^2,zx,zy),(zx,(z+y)^2,xy),(zy,xy,(z+x)^2)|=2xyz(x+y+z)^3 - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads

Using properties of determinants, prove that

`|((x+y)^2,zx,zy),(zx,(z+y)^2,xy),(zy,xy,(z+x)^2)|=2xyz(x+y+z)^3`

 

Advertisement Remove all ads

Solution

`|((x+y)^2,zx,zy),(zx,(z+y)^2,xy),(zy,xy,(z+x)^2)|=2xyz(x+y+z)^3`

L.H.S.

Multipiying R1, R2 and R3 by z, x, y respectively

`=1/(xyz)|(z(x+y)^2,z^2x,z^2y),(x^2z,x(z+y)^2,x^2y),(y^2z,xy^2,y(z+x)^2)|`

take common z, x, y from C1, C2, & C3

`=(xyz)/(xyz)|((x+y)^2,z^2,z^2),(x^2,(z+y)^2,x^2),(y^2,y^2,(z+x)^2)|`

C1 → C1 - C3 and C2  C2 - C3

taking common x+y+z from C1 & C2

`=(x+y+z)^2|((x+y+z),0,z^2),(0,z+y-x,x^2),(y-z-x,y-z-x,(z+x)^2)|`

R3 → R3 - (R1 + R2)

`=(x+y+z)^2|(x+y+z,0,z^2),(0,z+y-x,x^2),(-2x,-2zx,2xz)|`

C1 → zC1, C2 → xC3

`=(x+y+z)^2/(xz)=|(z(x+y-z),0,z^2),(0,x(z+y-x),x^2),(-2xz,-2zx,2xz)|`

C1 → C1 + C3   C2 → C2 + C3

 

 

`=(x+y+x^2)/(xz)|(z(x+y),z^2,z^2),(x^2,x(z+y),x^2),(0,0,2xz)|`

taking z and x common from R1 & R2

`=(x+y+x)^2/(xz)xxzx|(x+y,z,z),(x,z+y,x),(0,0,2xz)|`

expansion along R3

= (x+y+z)2 × 2xz ((x + y) (z + y) – xz)

= (x+y+z)2 × 2xz (xz + xy + yz + y2 - xz)

= (x+y+z)2 × 2xz (xy + yz + y2)

= 2xyz (x + y + z)3

Concept: Properties of Determinants
  Is there an error in this question or solution?
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×